A Comparative Review on Low-Cost Adsorbent based Alkali-Activated Materials by Adsorption Study - F.F. Kamarzaman; M.M. Al Bakri Abdullah; M.R. Rozainy; R. Ahmad; W.M.W. Ibrahim; M.F. Omar; C.M.R. Ghazali; W.M.A.W. Ibrahim (Archives of Metallurgy and Materials)
The degradation of the condition of wastewater is becoming more and more serious due to the endless development. One of the main reasons is heavy metal contamination, which causes significant harm to the climate and humanity, such as bad health consequences, environmental degradation, and air pollution. Adsorption, which uses proven adsorbents such as activated carbon, is one of the most common methods for heavy metal removal in wastewater. However, since activated carbon is very expensive to build and repair due to complex production, most people choose another material to overcome this problem. Researchers have recently focused on finding low-cost adsorbents, which are typically industrial, agricultural and food wastes that can generate in large quantities. However, Alkali-Activated Materials (AAMs) have been recognized as a novel possible adsorbent because they are cheap, made from solid aluminosilicate and extremely alkaline activator solution, making them appropriate for usage in the civil engineering specialty. Moreover, they have become an option for various applications due to their unique geopolymer structure, which is highly mechanically, chemically and thermally stable. Hydroxyapatite (HAP) can be extremely useful in this application, as it is a promising biomaterial that has great potential for a low-cost AAMs adsorbent. The purpose of this study is to analyze the present development of a potential economic alternative adsorbent, particularly based on alkali-activated materials (known as geopolymers), for the elimination of heavy metal pollutants in wastewater using adsorption techniques.